RENTENIR: Alternatif Kredit Bagi Pedagang Muslim Di Kota Langsa Pada Masa Pandemi COVID-19 - M. Yahya (Jurnal Samudra Ekonomika, 2021)
The Covid-19 pandemic is an opportunity for moneylenders to influence potential customers to borrow money from moneylenders with an easy and fast loan process. This paper aims to describe the phenomenon of moneylenders in Langsa City during the covid-19. The qualitative method in this study uses primary data in the form of interviews with Muslim traders in Langsa City who are directly involved with moneylenders. The results of this study indicate that moneylenders have played their role in the economic situation of the declining traders to get more benefits from the customers and the loan models offered are varied, the loan offers are easy and the process is fast enough with an ID card to be an attraction for Muslim traders, plus The Covid-19 condition has increasingly convinced the Muslim traders of Langsa City to make loans to moneylenders even though they know that loan interest is high.